PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN PADA KELOMPOK USAHA KECIL MENENGAH (UKM) DESA SUKAJADI - Denia Maulani; Ayu Wulandari; Niken Octaviani; Putri Endang Sukaesih (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2023)
Small and Medium Enterprises (SMEs) are the most important economic activities to prevent competition from unfair competition. The place for community service that we chose was Sukajadi Village, precisely in kp. Gadog Sisi RT 03/RW 08, Tamansari District, Bogor Regency. The problem faced by SMEs is the lack of ability of SMEs in managing finances. The purpose of this community service is to make SME actors (Tempe SMEs, Kue Noga SMEs, Convection SMEs, and Strawberry Seed SMEs) aware of the importance of recording financial reports on central performance. The method used is to socialize the importance of financial reports for SMEs and provide assistance in preparing financial reports for SMEs. The result of this activity is that SMEs can know the importance of preparing financial reports that will make it easier for them in the future to prepare financial reports correctly. With the preparation of this simple financial report, SME entrepreneurs can share their own assets and their business assets. SMEs can also see that developments gain or lose.